SIKAP POLITIK PRAWOTO MANGKUSASMITO TERHADAP PEMBUBARAN PARTAI ISLAM MASYUMI PADA MASA DEMOKRASI TERPIMPIN - Khuswatun Hasanah; Mhd. Alfahjri Sukri (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2022)
Soekarno's decision to simplify political parties during the Guided Democracy period resulted in a number of parties having to be dissolved or willing to dissolve themselves, including the Islamic-inspired political party, Masyumi. Prawoto Mangkusasmito, chairman of the Masyumi Islamic Party Center who opposed Soekarno's idea of guided democracy in the end chose to be loyal to Soekarno's decision, even though he tended to be considered semi-authoritarian. This study aims to explain Prawoto Mangkusasmito's political attitude towards the dissolution of the party which also had an impact on Masyumi. The method used in this research is descriptive method of historical analysis from a political approach perspective. Interpretation is generated through analysis of historical sources, related regulations, and literature studies. As a result, regarding political attitudes, even though he had fought for Masyumi, Prawoto remained loyal to the Presidential Decree No. 200 of 1960 concerning the Dismissal of the Masjumi Political Party; including parts / branches / branches throughout the territory of the Republic of Indonesia. His support for the dignity of the republic was clear, consistent and calculating. His political stance is motivated by the idea that people who fight for Islam and aim to uphold Islamic law should not be violated by Muslims in power. His thinking is optimistic that one day the policy of disbanding the party will change to a policy of reviving the party with efforts to uphold law and aspects of justice.